Forging Pathways to Success: Innovative Approaches to Private Higher Education in Central Java - Bhimo Widyo Andoko; Nano Prawoto; Sri Handari Wahyuningsih; Indah Susilowati (Media Ekonomi dan Manajemen, 2024)
This research identifies leadership styles at private universities in Central Java, analyzes organizational culture, and formulates strategies for the success/survival of private universities. Primary data was obtained through in-depth interviews with 9 university leaders as informants, with stratified sampling based on excellent, excellent, and good accreditation categories. Semi-structured interviews focused on leadership approaches, organizational culture, success strategies, and challenges. The data were analyzed using ATLAS.TI with thematic analysis. The results show that private universities have characteristics, such as leadership styles, that form different organizational cultures. There are differences in higher education management strategies between accreditation categories, especially in strategic priorities according to institutional goals. Superiorly accredited universities tend to prioritize research excellence, international collaboration, and innovative academic programs. The implication is that understanding the relationship between leadership, organizational culture, and strategic priorities can help universities align these elements for optimal effectiveness in achieving success in the competitive environment of higher education.